Early education and care, and reconceptualizing play - Reifel, Robert Stuart; Brown, Mac H. (Amsterdam ; New York : JAI, 2001)
This volume addresses two major areas of inquiry in the field of early childhood education and care. The first section of the book includes scholarly reviews on early childhood education and care and its conceptual bases. Programme curriculum and implementation are explored, including theoretically driven programmes and programme evaluations. Traditional perspectives on early childhood outcomes are detailed, alongside comparative analyses of early childhood practice from an international perspective. Section two presents the first in a series on reconceptualizing play. Traditional views of play, as an abiding element of early childhood practice, are critiqued. Questions about conceptions of play are raised by historical, ethical, cross-cultural, narrative, and theoretical treatments of play practices. These views are designed to stimulate thought about our most basic ideas of play and children.
Introduction / Stuart Reife -- Globalization and its discontents: early childhood education in a new world order / Sally Lubeck, Patricia A. Jessup, Abigail M. Jewkes -- Child care quality: a model for examining relevant variables / Eva L. Essa, Melissa M. Burnham -- Professional development and the quality of child care: an assessment of Pennsylvania's child care training system / Joyce Iutcovich, Richard Fiene, James Johnson, Ross Koppel, Frances Langan -- Professional caring as mothering / Noelene McBride, Susan Grieshaber -- The thematic unit: old hat or new shoes? / C. Stephen White, Greta G. Fein, Brenda H. Manning, Anne Daniel -- "Air is a kind of wind": argumentation and the construction of knowledge / Sue Dockett, Bob Perry -- "We don't play that way at preschool": the moral and ethical dimensions of controlling children's play / Mac H. Brown, Nancy K. Freeman -- The dangerously radical concept of free play / David Kuschner -- Play and diverse cultures: implications for early childhood education / Jaipaul L. Roopnarine, James E. Johnson -- Under the lens: the play-literacy relationship in theory and practice / Kathleen A. Roskos, James F. Christie -- The play frame and the "fictional dream": the bidirectional relationship between metaplay and story writing / Jeffrey Trawick-Smith.
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: Early childhood education; Child care; Play; Pre-school & kindergarten; Child & developmental psychology; Education -- Preschool & Kindergarten